EBV Reactivation and Chromosomal Polysomies: Euphorbia tirucalli as a Possible Cofactor in Endemic Burkitt Lymphoma - Susanna Mannucci; Anna Luzzi; Alessandro Carugi; Alessandro Gozzetti; Stefano Lazzi; Valeria Malagnino; Monique Simmonds; Maria Grazia Cusi; Lorenzo Leoncini; Cornelia A. van den Bosch; Giulia De Falco (Advances in Hematology)
Burkitt lymphoma is endemic in the Equatorial Belt of Africa, its molecular hallmark is an activated, MYC gene mostly due to a chromosomal translocation. Especially in its endemic clinical variant, Burkitt lymphoma is associated with the oncogenic Epstein-Barr virus (EBV), and holoendemic malaria acts as an amplifier. Environmental factors may also cooperate in Burkitt lymphomagenesis in the endemic regions, such as plants used as traditional herbal remedies. Euphorbia tirucalli, a plant known to possess EBV-activating substances, has a similar geographical distribution to endemic Burkitt’s Lymphoma and is used as a hedge, herbal remedy and toy in the Lymphoma BeltI. In this study we aimed at determining if exposure to Euphorbia tirucalli could contribute to lymphomagenesis, and at which extent. Lymphoblastoid and cord blood-derived cell lines were treated with plant extracts, and the expression of EBV-coded proteins was checked, to assess EBV reactivation. The occurrence of chromosomal translocations was then investigated by FISH. Our preliminary results suggest that E. tirucalli is able to reactivate EBV and determine chromosomal alterations, which leads to c-MYC altered expression. The existence of genomic alterations might determine the accumulation of further genetic alteration, which could eventually lead to a transformed phenotype.